KEANEKARAGAMAN JENIS KELELAWAR (Chiroptera) DI KAWASAN UNIVERSITAS TANJUNGPURA KOTA PONTIANAK - Safitri, Zunia; Prayogo, Hari; Erianto, Erianto (Universitas Tanjungpura, 2020)
Bat (Chiroptera) are a type of mammal that has an important ecological role for the sustainability of the forest, including helping to spread seeds, flower pollination, and control insect population. Bats have adapted well to various habitats, including urban forests. The purpose of this research is to search bats diversity data in the area of Tanjungpura University, Pontianak. Method of this research using the capture and release by using a mist net, placed purposively, by looking at the bat path. The Mist net was installed around tree canopy layers at 3 research locations, new campuses, old campuses, and the Arboretum. Based on the location of the observation, the number of species and types found in three locations is the same. There are 2 species of the family Pteropodidae including the sub-order Megachiroptera, Cynopterus brachyotis and Cynopterus minutus. Data analysis results show that no type of bat dominates from three observation locations, the dominance index is < 1. Diversity of Bats from all three locations shows < 1 which includes low diversity index criteria. The evenness of bats from all three observation locations has a criteria value of > 0.5 meaning the community at all three observation locations is the lability community to the stable. Keyword: Bats, Diversity, Urban Forest